Tinjauan Hukum Islam tentang Upaya Wanita Karir dalam Mewujudkan Keluarga Sakinah: Studi Kasus Dosen Wanita Akademi Kebidanan Ibrahimy Sukorejo Situbondo - Mawardi Mawardi (Program Pascasarjana Universitas Ibrahimy, 2019)
People are the noblest creatures of Allah, who have gharizah al-fitriyyah (aptitude) and have love with others and the opposite sex in their household life. When a woman has a career, she has a double responsibility as a wife. From that phenomenon, there are several problems in this research. They are how is the understanding of the female lecturers at Akbid Ibrahimy about sakinah family? How are their efforts to create a sakinah family? And how are career women’s efforts in realizing a sakinah family from Islamic law perspective? This research uses a descriptive qualitative approach, which describes some data obtained from the field by interview, observation, and documentation. Then followed by the editing, classifying, and analyzing process. Female lecturers’ efforts in realizing a sakinah family from the Islamic law perspective is they are permissible to initiate a career according to her expertise and motivation but must prioritize the family. She must be able to provide good control and service to her husband and children so that her responsibilities in the household and in the work are equally balanced.